A study on different techniques in ALPR system : The systems performance analysis - Vi, Gan Vi; Ahmad Afif, Mohd Faudzi (Springer Science and Business Media Deutschland GmbH, 2022)
License plate recognition and localization are crucial steps in most transportation applications. For instance, trace for stolen vehicles, speed or airport gate monitoring, road traffic monitoring and car parking control. This is required a system to extract automatically and recognize the character of the license plate from the image captured. The automatic license plate recognition (ALPR) system has aroused great interest in the research community, because in certain regions, cities or countries have certain limitations and lack of similarity between different license plates. The ALPR system includes three important components: first step is license plate localization, second step is character segmentation and third step is character recognition. This paper is to give comprehensive reviews of the localization and recognition techniques involved in the license plate recognition system and compares existing effective solutions.